La práctica de valores y la disciplina en los niños y niñas de la Escuela Fiscal Mixta "24 de Octubre", del recinto Azanloma, cantón Chillanes, provincia Bolívar, año lectivo 2010- 2011 - Galeas Gaibor, Verónica Cecilia (2011)
The present research work on " ETHICAL PRACTICE AND THE DISCIPLINE IN CHILDREN OF THE JOINT FISCAL SCHOOL" October 24 ", exhibition AZANLOMA, Canton Chillanes, Bolivar Province, 2010-2011. "Is only intended to constitute an alternative solution to that complicated difficulty presented in the Canton schools, especially in children of school" October 24, where it is found that discipline was a problem because of lack of application of ethical values as a strategy for creative problem solving and to contribute appropriately to the development of the institution. Was determined as a starting point the same as that favored the development of the research, background, allowing us to identify the reality of an educational problem, which has fought long and so far no awareness has been achieved for teachers to achieve beyond the levels we would have liked in the application of an ethical guide that exceeded the discipline of children in school, "October 24". The problem identified is consistent with the environment in which education takes place in classrooms with children of school "October 24". The response to the lack of application and importance of ethical values by teachers is considered as reinforcement in educational work since, theoretically apply even worse examples, simply go unnoticed in the daily work in classrooms of classes. Fully argue that the degree work, noting the importance, necessity, relevance, originality and feasibility. In context where the research work, of course resistance was found in teachers and parents to gather information. This is understood by the very fact that the issue is very delicate and complex. According to these parameters we propose the general and specific objectives; they have a high degree of validity, reliability and enforceability to achieve its scope and measuring, hypothesis testing, which allowed us to identify two variables that were conveniently operational zed according to its parameters. XIV All this development Operationalization helped us have the necessary elements to develop the data collection instruments. In Chapter I, theoretical framework, we describe issues directly related to the reason for the research, which are discipline and ethical values applied to children of school October 24 as the solution of problems, we also describe the principles, kinds of ethical values that have a special relationship in scientific theory. In Chapter II, we describe the methods that we support the organization and execution of our work, methods that were for the purpose, by level, location, inductive and historical analog, presented in an easy to follow, that finally we have a feasible degree of appreciation and purpose, prior to determining the type of research, selection and decision of the universe and our relationship that we built for the school applied to the research subjects, which was in full (2 teachers, 30 students) for a measurable population. Chapter III details the results obtained after the survey, they were tabulated in a thorough and configure them relevant charts and graphs, then interpret them qualitatively. This allowed to reach the testing of the hypothesis and draw our own conclusions based on that make our recommendations. Finally, in chapter IV of this research work We provide the proposed building on the results of the surveys that applies to teachers and children of school October 24 in which it was noted that relevant do not care Application for solving ethical discipline. As can be seen this paper investigates the reality is that development of the discipline in the institution. Not only establishes a diagnosis of this reality but also requires theoretical and practical problems and a proposal for the classroom, allowing effectively incorporate ethical values that help overcome the discipline so that students are active in, its development and consequently, will become a decisive contribution in their teacher training.